Simultaneous approximation for the Phillips operators - N. K. Govil; Vijay Gupta; Muhammad Aslam Noor (International Journal of Mathematics and Mathematical Sciences, 2006)
We study the simultaneous approximation properties of the well-known Phillips operators. We establish the rate of convergence of the Phillips operators in simultaneous approximation by means of the decomposition technique for functions of bounded variation.